Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, November 22, 1929 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1929)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, November 22, 1929. Hawley was determined to have Warner with him, and as the year waned, he renewed the urging. Warner was to graduate the following June and contemplated the study of law. Hawley wanted him to take up the study with Hooker and himself. Above all, he believed Warner would find social advancement easy in Hartford. He advised him practically to remain heart-whole and fancy-free until he could establish himself in Hartford, where a matrimonial union that would be immensely successful in both sentimental and practical aspects would be easy. The new law firm of Hawley and Hooker found Hartford a satisfactory field. Hawley had taken the measure of the Connecticut political situation. He found few giants in official places and felt sure that courageous and determined men could leave there impress on the states affairs. On November 9, Hawley wrote Warner discussing all of this.
1 electronic record. Scanned newspaper article. 1 image scans. 919 KB (941,196 bytes) 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19).
Keywords: United States--History--Civil War, 1861-1865; Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); Letters; Personal correspondence; Newspapers